Factor Analysis of Caesarean Section at Panti Waluya Hospital, Malang - Pertiwi Perwiraningtyas; Anita Rahmawati (Journal of Ners and Midwifery, 2021)
The incidence of caesarean section in Indonesia has increased every year. Caesarean section is an alternative to delivery when vaginal delivery cannot be done. The problems studied are the factors that influence the action of cesarean section delivery. The purpose of the study was to analyze the factors of delivery by caesarean section at Panti Waluya Hospital, Malang. The design of the study used cross sectional. The population in this study was all parturition mothers who were in the medical records of Panti Waluya Hospital Malang in January-May 2021. The sampling technique in this study used Simple Radom sampling, obtained 55 samples that met the inclusion criteria (ie data in the medical record). The study was carried out at the Panti Waluya Hospital in Malang in May 2021. The instrument used observation sheet. The data taken came from secondary data, namely the patient's medical record. The independent variables of the study were maternal age, gestational age, employment status, parity, disease history, income, insurance, education, delivery distance. The dependent variable of the study was caesarean section. The data analysis used Fisher exact test and logistic regression test. The results showed that history of disease and delivery interval had a significant correlation with delivery, and the variable that was the determinant of CS delivery was history of disease (p=0.012; OR=8.463). It is necessary to carry out routine ANC for pregnant women, in order to avoid risk factors for childbirth by caesarean section.